David Kimhi’s study of םיהולא in his book of roots analysed from an exegetical perspective - Oseka, Matthew (Vox Scripturae - Revista Teológica Internacional, 2017)
The present paper explores David Kimhi’s (ק״דר) study of הולא and םיהולא contained in his Book of Roots (םישרשה רפס) which, on the one hand, utilised the legacy of earlier lexicographers, on the other hand, expanded the Hebrew scholarship in this regard. Kimhi’s elucidation of םיהולא is situated against ancient biblical translations (Targumim, the Septuagint cum its revisions) and against the classic Jewish literature (Midrashim, Mekhiltas, Pirkes, Yalkutim, the Babylonian Talmud) and commentaries.